Antibiotics Resistance Pattern of Food-Borne Bacteria Isolated from Ice Cream in Bangladesh: A Multidisciplinary Study - Md Sohel; Moushumi Akter; Md. Fahmid Hasan; Shahin Mahmud; Mohammod Johirul Islam; Ashekul Islam; Khairul Islam; Abdullah Al Mamun (Journal of Food Quality)
Ice cream is one of the most popular food items consumed during the summer season in Bangladesh by all ages but mostly school-going students. Due to the ingredients and handling process of ice cream, it acts as a good shelter for pathogenic and nonpathogenic microorganisms. Therefore, we aimed to investigate the microbial count, prevalence, isolate and characterize multidrug-resistant bacteria in ice cream samples collected from nearby shops of schools in Tangail district, Bangladesh. Ice-cream consumer and nonconsumer students were selected by providing questionnaires. Total viable count (TVC) and total coliform count (TCC) were determined by pour plate methods, where conventional methods were performed for bacterial identification. The Kirby-Bauer disk diffusion method was used to determine the antimicrobial susceptibility of bacterial isolates. Kado and Liu method, with some modifications, was used to extract plasmid from the isolated bacteria and visualized through gel electrophoresis. The demographic characteristics showed that the degree of symptoms regarding microorganisms mediated disorders and rate of antibiotics intake in ice cream consumers were significantly higher than the nonconsumers. The range of TVC and TCC in the ice cream samples was found 0–9.9 × 109 CFU/ml and 0–900 CFU/ml, respectively. Interestingly, 93.75% of the total ice cream samples also showed fungal positive. A total of 12 different bacterial species were identified, including Proteus spp, E. coli, V.cholera, Pseudomonas spp, Shigella spp, Klebsiella spp, Aeromonas spp, V. Parahemolyticus. Salmonella paratyphi, Citrobacterspp, Plesiomonasspp, and Staphylococcus aureus. The antimicrobial susceptibility assay showed the multiple resistance frequency of these isolates to different antimicrobial drugs. All individual isolates were screened for plasmid DNA, and we found that seven strains harbored a single or more than two plasmids sized approximately between 1.9 and 140 MDa, indicating a possible connection between resistance phenotype pattern and genotype.